Weed Seedbank Changes Associated with Temporary Tillage After Long Periods of No-Till - Fernando Oreja; Marianne Torcat Fuentes; Antonio Barrio; Dario Javier Schiavinato; Virginia Rosso; Elba de la Fuente (Agronomy, 2025)
Long-term no-till systems have led to shifts in weed communities and reduced the effectiveness of herbicide-based control. Occasional tillage is proposed as an alternative strategy to disrupt weed emergence patterns by redistributing seeds within the soil profile. This study aimed to evaluate the impact of occasional tillage on weed seedbank composition and vertical distribution of viable weed seeds and propagules within the soil profile, after more than 20 years of continuous no-till. A paired-plot experiment was conducted in Carlos Casares, Buenos Aires, Argentina, with three replications. Treatments included continuous no-till and occasional tillage (two disk harrow passes in August 2022 and April 2023) combined with three soil depths (0–5, 5–10, and 10–15 cm). Soil samples were collected in spring 2022 and fall 2023, and weed emergence was recorded under semi-controlled conditions. Overall species richness did not differ significantly between tillage treatments but was consistently greater in the upper 0–5 cm soil layer. Weed abundance also declined with depth. Five species, Chenopodium album, Stellaria media, Eleusine indica, Oxybasis macrosperma, and Heliotropium curassavicum, were frequent across treatments. Some species were exclusive to either no-till or tilled plots, for example, Datura ferox, Poa annua, and Veronica peregrina were found only in tilled plots, while Portulaca oleracea, Medicago lupulina, and Trifolium repens were exclusive to no-till plots. These results indicate that occasional tillage alters species composition and vertical seed distribution in the seedbank without significantly reducing total richness or abundance, offering an additional, but not always effective, tool to influence weed community structure in no-till systems.